1985
DOI: 10.1055/s-2007-969500
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zur endokrinen Wirksamkeit von Inhaltsstoffen ausCimicifuga racemosa2.In vitro-Bindung von Inhaltsstoffen an Östrogenrezeptoren

Abstract: The endocrine activity of compounds of the rhizome of CIMICIFUGA RACEMOSA can be demonstrated in the IN VIVO model of the ovariectomized rat as well as in the IN VITRO system of the estrogen receptor assay. A reduction of the serum levels of luteinizing hormone in ovariectomized rats takes place upon application of a methanol-extract. This extract contains substances, which are able to bind to estrogen receptors of rat uteri. Using the estrogen receptor assay as a pharmacological testsystem to determine the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The mechanism occurred through competitive inhibition of oestrogen following the selective binding of oestrogen receptors (ERα) on the hypothalamus and pituitary [ 52 ]. An earlier study found contrary results for reduction of LH, however this study investigated an isolated flavonoid and suggested that other constituents may be active [ 37 ].…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The mechanism occurred through competitive inhibition of oestrogen following the selective binding of oestrogen receptors (ERα) on the hypothalamus and pituitary [ 52 ]. An earlier study found contrary results for reduction of LH, however this study investigated an isolated flavonoid and suggested that other constituents may be active [ 37 ].…”
Section: Resultsmentioning
confidence: 72%
“… Three RCTs demonstrate positive fertility effects for Cimicifuga racemosa in women with PCOS [ 65 , 67 , 68 ] Ethanol extract Klimadynon® 1. One study investigated a constituent flavonoid of Cimicifuga racemosa , discovered during the course of the study for reduction for LH in ovariectomised rats [ 37 ] 1. Binds with α oestrogen receptors [ 44 ] in the pituitary and reduces LH secretion [ 45 , 52 , 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…During the last years Cimicifuga racemosa (L) Nuttal (Ranunculaceae) has become one of the most important plants in the therapy of gynecological diseases (1). Triterpene glucos ides like 27-deoxyactein are characteristic for the rhizome (2)(3). Specific flavonoids are the isoflavone formononetine (2) and the faivone kaempferol (4).…”
mentioning
confidence: 99%
“…Triterpene glucos ides like 27-deoxyactein are characteristic for the rhizome (2)(3). Specific flavonoids are the isoflavone formononetine (2) and the faivone kaempferol (4). There is hardly any information about these flavonoids in extracts and medicines made from the rhizome.…”
mentioning
confidence: 99%
“…An absence of estrogenic effects as measured by the in vivo mouse uterotrophic assay has recently been demonstrated in studies using the same formulation of BCE employed herein (Mercado-Feliciano et al 2012), while the presence of a phytoestrogen (formononetin) in black cohosh rhizomes has been disputed (Avula et al 2009; Jarry et al 1985; Jiang et al 2006; Jiang et al 2011; Kennelly et al 2002; Panossian et al 2004). Interestingly, however, the effects of BCE in the present studies are very similar to the effects of the phytoestrogen genistein (a soy isoflavone) on the immune system of female B 6 C 3 F 1 mice (the same sex and strain used in these studies).…”
Section: Discussionmentioning
confidence: 78%